Training network administrators in a game-like environment. (July 2015) - Arslan, Engin; Yuksel, Murat; Gunes, Mehmet Hadi
Abstract: Management and automated configuration of large-scale networks is one of the crucial issues for Internet Service Providers (ISPs). Since incorrect configurations may lead to loss of an enormous amount of customer traffic, highly experienced network administrators are typically the ones who are trusted for the management and configuration of a running ISP network. In this paper, we present an online management and experimentation system with a "game" interface to train network administrators and explore what-if scenarios without having to risk the large-scale network operation. The interactive environment treats the trainee network administrators as players of a game and tests them with various failures or dynamics for real-time management and configuration of large-scale networks. To prototype the concept of "network management as a game", we modified NS-2 to establish an interactive simulation engine and connected the modified engine to a graphical user interface for traffic animation and interactivity with the player. We also conducted two user experiments using different learning methods and observed sizable improvement in the capabilities of trainees on the problem of interior gateway protocol link weight setting.